2008
DOI: 10.1371/journal.pcbi.1000061
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Timing Mechanisms Produce Discrete and Continuous Movements

Abstract: The differentiation of discrete and continuous movement is one of the pillars of motor behavior classification. Discrete movements have a definite beginning and end, whereas continuous movements do not have such discriminable end points. In the past decade there has been vigorous debate whether this classification implies different control processes. This debate up until the present has been empirically based. Here, we present an unambiguous non-empirical classification based on theorems in dynamical system th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
124
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(135 citation statements)
references
References 39 publications
(55 reference statements)
11
124
0
Order By: Relevance
“…For example, the movement speed-accuracy tradeoff was different in the two classes of movements (Smits-Engelsman et al, 2002), which seems to support the third hypothesis. On the other hand, a theoretical study suggested that discrete movement can be constructed from rhythmic movement (i.e., supporting the second hypothesis) by imposing timekeeper mechanisms on the controller (Huys et al, 2008).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, the movement speed-accuracy tradeoff was different in the two classes of movements (Smits-Engelsman et al, 2002), which seems to support the third hypothesis. On the other hand, a theoretical study suggested that discrete movement can be constructed from rhythmic movement (i.e., supporting the second hypothesis) by imposing timekeeper mechanisms on the controller (Huys et al, 2008).…”
Section: Introductionmentioning
confidence: 89%
“…The third hypothesis assumes that rhythmic and discrete movements are two different (or partially different) classes of movements (Sternad et al, 2000;Buchanan et al, 2003). These hypotheses have been examined from behavioral (Buchanan et al, 2003;van Mourik and Beek, 2004), theoretical (Schöner, 1990;Huys et al, 2008;Ronsse et al, 2009), and neuronal (Spencer et al, 2003(Spencer et al, , 2007Schaal et al, 2004) perspectives. The current consensus is that rhythmic movements are not mere concatenations of discrete movements (i.e., the first hypothesis has been ruled out).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the drift coefficients numerically express the system's vector field in phase space, that is, they allow recovery of the flow that allows for the unambiguous qualification of dynamical systems (cf. Strogatz 1994;Huys et al 2008 and averaged across blocks of 10 trials with adjacent ID e 's. From the first two drift coefficients (representing the velocity vector's x and y components), we determined for each bin the angles u between its neighbouring velocity vectors and extracted its maximum value (u max ).…”
Section: Methodsmentioning
confidence: 99%
“…In other words, phase flows capture the causation underlying the time evolution of such dynamical systems. Of late, the (topological) structure in phase flows has been used as a conceptual tool for the categorization of (discrete and rhythmic) movements (Huys, Studenka, Rheaume, Zelaznik, & Jirsa, 2008;Jirsa & Kelso, 2005). Phase flow patterns, however, may also underlie the perceptual recognition of distinct motor processes (Perdikis & Jirsa, 2010; see also Muchisky & Bingham, 2002).…”
mentioning
confidence: 99%